Development of an Interactive Flipbook Based E-Module on the Material of Norms in Society for Students of Grade II of Mayjend Elementary School Sutoyo SM Medan 2025/2026 Academic Year - Rini Ika Putri (Journal of Elementary School Education, 2026)
This study aims to develop an interactive flipbook-based E-Module on the material of norms in society for second-grade students of Mayjend Sutoyo Elementary School, SM Medan, and to determine its feasibility and practicality. The background of this study is based on the dominance of teacher-centered learning, the limited use of learning media, and the low understanding of students on the material of norms that tend to be abstract. Therefore, innovative, interactive learning media are needed, and are in accordance with the characteristics of elementary school students who are at the concrete operational stage. The method used in this study is Research and Development (R&D) with a 4D development model that includes the define, design, develop, and disseminate stages, but this study is limited to the develop stage. The research subjects were second-grade students of Mayjend Sutoyo Elementary School, SM Medan. The research instruments were validation questionnaires by media experts, language experts, and material experts, as well as teacher and student response questionnaires to measure the practicality of the product. The results of the study indicate that the developed flipbook-based interactive E-Module has a very high level of feasibility, with a validation percentage of media experts of 96%, language experts of 100%, and material experts of 95% which is included in the very valid category. In addition, the results of the practicality test showed a teacher response of 100% and a student response of 88% with a very practical category. Thus, the flipbook-based interactive E-Module is declared feasible and practical to be used as a learning medium. This media is able to increase student interest, involvement, and understanding, so it can be an alternative effective learning medium in elementary schools.